Key issues in implementing halal certification process in selected halal chicken slaughterhouses in Thailand - Sa-idi, Adib (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
The Halal certification process is one of the significant factors in the developing Halal food industry. The Halal certification process verifies Halal food production and also establishes trust with consumers. This research focuses on the implementation of the Halal certification process for selected Halal chicken slaughterhouses in Thailand. There are two main objectives of the research. The first objective is to study the process of Halal certification in chicken slaughterhouses in Thailand. The second objective is to study the problems in implementing the Halal certification process in selected Halal chicken slaughterhouses in Thailand. This research used a qualitative method, the data being divided into two types: primary and secondary. Primary data were collected through in-depth interviews and direct observation. Secondary data were collected from textbook, documents and published reports. The research found that the Halal certification process in chicken slaughterhouses in Thailand consists of five steps: 1. preparation; 2. application submission and consideration; 3. appointment of a Halal slaughtering supervisor to the chicken slaughterhouse to undertake the duties; 4. result analysis and approval of Halal certification; and 5. follow up and evaluation. For the implementation of the Halal certification process in selected Halal chicken slaughterhouses, the research found that the problems in implementing the process are divided into six categories: 1. problems caused by the Halal slaughtering supervisors; 2. problems caused by the employees in the factory; 3. problems in the slaughterhouses; 4. problem related to the checklist documents; 5. problem of incomplete auditing; and 6. problem of financial support. Based on the findings of this study, the suggestions are also divided into six categories: 1. improving the effectiveness of the Halal slaughtering supervisors; 2. improving the effectiveness of the employees in the chicken slaughterhouses; 3. improving the communication between the Halal slaughtering supervisors and the executive managers; 4. improving the Halal audit checklist and other documents especially reminder posters or notice boards at every critical point; 5. providing the Halal slaughtering supervisor with assistants or supporters; and 6. obtaining more financial support for the Halal certification process from the government sector. The suggestions form the basis of developing the Halal certification process, especially for chicken slaughterhouses in Thailand.